Evaluation on stability and thermophysical performances of covalently functionalized graphene nanoplatelets with xylitol and citric acid - Shazali, Siti Shafiah; Rozali, Shaifulazuar; Amiri, Ahmad; Zubir, Mohd Nashrul Mohd; Sabri, Mohd Faizul Mohd; Zabri, Mohd Zakuan (Elsevier, 2018)
An economical and environmentally friendly approach has been introduced to synthesize highly stable graphene nanoplatelets (GNPs) dispersions with different solvents e.g. water, ethylene glycol, methanol, ethanol, and 1-hexanol. The strategy involved with the introduction of hydroxyl groups through mild oxidation of GNPs which was then grafted with citric acid and xylitol that polymerized together, improving the solubility of GNPs. The functionalization of GNPs was proved by Fourier transform infrared (FTIR), Raman spectroscopy and high resolution-transmission electron microscope (HRTEM). Further study was carried out by using xylitol and citric acid (XC)-treated GNPs as an additive in base fluid to check their thermophysical properties. Great stability for water-, methanol-, ethanol-, 1-hexanol- and ethylene glycol-based XC-treated GNPs dispersions at 0.01 wt% was achieved, representing stable weight concentrations of 89%, 75%, 72%, 64% and 82% after 15 days, respectively. In addition, the XC-treated GNPs show remarkable enhancement in the thermal conductivity up to 34% at 60 °C. Furthermore, water-based XC-treated GNPs dispersions with different concentrations show Newtonian behaviour.